Characterization of purine catabolic pathway genes in coelacanths. Issue 6 (3rd June 2013) - Forconi, Mariko; Biscotti, Maria Assunta; Barucca, Marco; Buonocore, Francesco; De moro, Gianluca; Fausto, Anna Maria; Gerdol, Marco; Pallavicini, Alberto; Scapigliati, Giuseppe; Schartl, Manfred; Olmo, Ettore; Canapa, Adriana; et al.
ABSTRACT Coelacanths are a critically valuable species to explore the gene changes that took place in the transition from aquatic to terrestrial life. One interesting and biologically relevant feature of the genus Latimeria is ureotelism. However not all urea is excreted from the body; in fact high concentrations are retained in plasma and seem to be involved in osmoregulation. The purine catabolic pathway, which leads to urea production in Latimeria, has progressively lost some steps, reflecting an enzyme loss during diversification of terrestrial species. We report the results of analyses of the liver and testis transcriptomes of the Indonesian coelacanth Latimeria menadoensis and of the genome of Latimeria chalumnae, which has recently been fully sequenced in the framework of the coelacanth genome project. We describe five genes, uricase, 5‐hydroxyisourate hydrolase, parahox neighbor B, allantoinase, and allantoicase, each coding for one of the five enzymes involved in urate degradation to urea, and report the identification of a putative second form of 5‐hydroxyisourate hydrolase that is characteristic of the genus Latimeria. The present data also highlight the activity of the complete purine pathway in the coelacanth liver and suggest its involvement in the maintenance of high plasma urea concentrations. J. Exp. Zool. (Mol. Dev. Evol.) 322B: 334–341, 2014. © 2013 Wiley Periodicals, Inc.